Podręcznik w nauczaniu języka obcego. Wnioski z analizy wybranych podręczników do nauki języka niemieckiego. - Zenderowska-Korpus, Grażyna (Neofilolog, 2019)
The aim of the article is to present textbooks for learning German as a foreign language that have been approved for school use by the Ministry of Education. The first part deals with different criteria for evaluation of textbooks and didactic materials. Additionally, it provides the Ministry of Education textbook suitability requirements. The second part presents the end results of an analysis which involved textbooks for learning German. It also contains a summary of questionnaires conducted among students and teachers. The summing-up offers reflections and conclusions concerning the features of an optimal textbook for learning a foreign language.